2019
DOI: 10.2196/13864
|View full text |Cite
|
Sign up to set email alerts
|

Mobile and Connected Health Technology Needs for Older Adults Aging in Place: Cross-Sectional Survey Study

Abstract: Background An increasing number of mobile and wearable devices are available in the market. However, the extent to which these devices can be used to assist older adults to age in place remains unclear. Objective This study aimed to assess older adults’ perceptions of using mobile and connected health technologies. Methods Using a cross-sectional design, a total of 51 participants were recruited from a senior community center. Demographics an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 39 publications
6
27
0
Order By: Relevance
“…The relevant questions on sharing health data were not asked at the 6-week interview, so it did not appear in the 6-week discussion. The results are consistent with the findings of previous studies that older adults would like to share their tracked health data with health care providers, friends, and family members [ 41 ]. Their willingness to share health data with health care providers may help the physician-patient dyad to better improve patient health outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…The relevant questions on sharing health data were not asked at the 6-week interview, so it did not appear in the 6-week discussion. The results are consistent with the findings of previous studies that older adults would like to share their tracked health data with health care providers, friends, and family members [ 41 ]. Their willingness to share health data with health care providers may help the physician-patient dyad to better improve patient health outcomes.…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, some older adults are passionate about acquiring new forms of technological skills that can aid them in maintaining their independence as well as their quality of life [ 29 ]. This is similar to a previous study in which it was reported that more than 80% of community-dwelling older adults expressed interest in using health technology [ 52 ].…”
Section: Discussionsupporting
confidence: 91%
“…The role of a digital navigator is 3-fold: (1) evaluate HITs, such as apps, and make appropriate recommendations to health professionals; (2) set up technology and troubleshoot with the consumer, thereby allowing the health professional to focus on the clinical interaction with the consumer; and (3) interpret and report salient data collected by the HIT to both the consumer and the health professional in a user-friendly way to inform care and self-management. Although the current use of HITs among older adults is relatively low, this does not appear to be due to lack of interest [20] but rather due to the need for education and training in relation to the potential benefits of HITs and the practicalities of engagement with these technologies [57]. As such, a digital navigator has the potential to be particularly impactful for the older adult community, including both for consumers and their families and for health professionals.…”
Section: The Potential Impact Of Health Information Technologiesmentioning
confidence: 99%